A Study of Relationship between Environmental Awareness and Scientific Attitudes among Higher Secondary Students - Yadav, Paramanand Singh; Bharati, Anita (JOURNAL OF INDIAN EDUCATION, 2007)
The present world is witnessing a number of environmental crises, which are the result of the unmindful exploitation of natural resources by human being. There is an urgent need to create environmental awareness among all human beings to conserve, protect and nurture our environmental resources. Consequently, environmental education is included in school curriculum right from the very beginning. The present study was conducted to study the environmental awareness among higher secondary students of Varanasi district of Uttar Pradesh. The findings of the study indicated that environmental awareness has positive relationship with scientific attitude among students and science students were found more aware about their environment as compared to arts students.